Factors influencing online collaborative learning: Why some groups take off better than others? - Mama, Maria; Demetriou, Skevi; Ioannou, Andri (My University, 2013)
In this work we carried out a case study to understand how some groups “take off” better than others with regards to engaging in the collaborative knowledge construction process in a virtual learning setting. We found that student facilitation was an important contributor to the process. Instead, the contribution of “lower” quality initial postings can jeopardize the process.
Keywords: Collaborative knowledge; Virtual learning